Treatment of a patient with massive osteochondral exostosis of the radial neck: clinical case - Ivan A. Vasilyev; Musa N. Maysigov; Alexey N. Logvinov; Alexander V. Frolov; Dmitry A. Bessonov; Dmitry O. Ilyin; Andrey V. Korolev (Клиническая практика)
BACKGROUND: Osteochondroma (osteochondral exostosis) is the most common benign neoplasm of bone tissue, accounting for up to 9% of all bone tumors. Possible manifestations of a single osteochondral exostosis are pain, a limited range of motion, compression of vascular or neural structures, and crepitus. The literature describes several clinical cases of the treatment of patients with osteochondral exostosis of the proximal radius. A distinguishing feature of the proximal radius’s anatomy is the close location of such anatomical structures as the posterior interosseous nerve, the enthesis of the distal biceps tendon, and the proximal radioulnar joint.